Babesia microti Infection Changes Host Spleen Architecture and Is Cleared by a Th1 Immune Response - Djokic, Vitomir; Akoolo, Lavoisier; Parveen, Nikhat (Frontiers in Microbiology, 2018)
Babesia microti is a malaria-like parasite, which infects ~2000 people annually, such that babesiosis is now a notifiable disease in the United States. Immunocompetent individuals often remain asymptomatic and are tested only after they feel ill. Susceptible C3H/HeJ mice show several human-like disease manifestations and are ideal to study pathogenesis of Babesia species. In this study, we examined parasitemia of B. microti at different time points and assessed its impact on hemoglobin levels in blood, on spleen pathology and overall immune response in C3H/HeJ mice. Peak parasitemia of 42.5% was immediately followed by diminished hemoglobin level. Parasitemia at 21 days of infection was barely detectable by microscopy presented 5.7x108 to 5.9x109 B. microti DNA copies confirming the sensitivity of our qPCR. We hypothesize that qPCR detects DNA released from recently lysed parasites or from extracellular B. microti in blood, which are not easily detected in blood smears and might result in under-diagnosis of babesiosis in patients. Splenectomized patients have been reported to show increased babesiosis severity and result in high morbidity and mortality. These results emphasize the importance of splenic immunity in resolution of B. microti infection. Splenomegaly in infected mice associated with destruction of marginal zone with lysed erythrocytes and released B. microti life forms in our experiments support this premise. At conclusion of the experiment at 21 days post-infection, significant splenic B and T cells depletion and increase in macrophages levels were observed in B. microti infected mice suggesting a role of macrophage in disease resolution. Infected mice also showed significantly higher plasmatic concentration of CD4 Th1 cells secreted cytokines such as IL-2 and IFN-γ while cytokines such as IL-4, IL-5, and IL-13 secreted by Th2 cells increase was not always significant. Thus, Th1 cells-mediated immunity appears to be important in clearance of this intracellular pathogen. Significant increase in IL-6 that promotes differentiation of Th17 cells was observed but it resulted in only moderate change in IL-17A, IL-17F, IL-21 and IL-22, all secreted by Th17 cells. A similar immune response to Trypanosoma infection has been reported to influence the clearance of this protozoan, and co-infecting pathogen(s).